Integrasi Nilai-Nilai PAK (Pendidikan Agama Kristen) dalam Kehidupan Masyarakat Beragama - Kezia Almanda Oni Eki; Nur Lestari; Semuel Linggi Topayung; Efiana Manilang (Berkat : Jurnal Pendidikan Agama dan Katolik, 2024)
This Study explores the important role of Cristian Education (PAK) values ​​in the lives of diverse communities. Within the framework of pluralism, values ​​such as love, tolerance, and justice are key to creating interfaith harmony. With a qualitative approach, this study examines how PAK values ​​are applied in social interactions, education systems, and community activities.The results of the study indicate that the application of PAK values ​​not only strengthens Christian identity, but also supports positive dialogue between religious communities. The conclusion of this article confirms that the integration of PAK values ​​can serve as a bridge to building a more inclusive and peaceful society, and reduce the risk of conflict in diversity.